If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-9,2)(-10,-4)=0
We simplify the equation to the form, which is simple to understand
(-9,2)*(-10,-4)=0
Reorder the terms in parentheses
multiplication of parentheses
(+92)=0
Remove unnecessary parentheses
+92=0
We move all terms containing to the left and all other terms to the right.
0=0-92
We simplify left and right side of the equation.
0=-92
0=-92
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 4x^2+4x+9=0 | | 7m=5+8m | | 9t-14=-26+5t | | 3(k+2)=21 | | x^2-kx+3=0 | | x-0.8=8.29 | | 2u^2-3u+1=0 | | (2x-5)(3x-2)= | | 20z=100 | | 9x+10x=21 | | 4(x+7)=52 | | m^2-20m-14=0 | | 15xx+14x=8 | | 9(4x-1)=27 | | 6x^2+17x=0 | | 5x-3-7x=15-x | | 16x^2-8x-24=0 | | 3a+5=2a+15 | | 9(2n-5)= | | 3X^4+48x^2=0 | | 3-x+4=56+8x | | x=x-31+31 | | 4x-(7+x)=14 | | 14-(2q+5)=-2(4x-7) | | -25(10-x)=25x | | 6x+8-2x=10-11x-12 | | 10=6n+4n | | 10+7x=2+5x+2x | | 4-5-2x=87x-20 | | 4f-23+4f=-8 | | lg(6-x)=2lgx | | -6(s+11)=24 |